A Study Of Sintering Hematite Iron Ore Mixtures - M. Boucraut (Society for Mining, Metallurgy & Exploration, 1968)
The authors investigate the influence of the basicity index CaO / Si02 on the sintering properties of hematite ore mixtures. The experimentation was performed with three different mixtures of ores from Tazadit, Nimba, Mano-River, Itabira, Marcona, Goa, Mapawa and Cassinga. Increasing the basicity index CaO / Si02 between 0.1 and 3, chiefly through limestone admixture makes possible to reduce the thermal consumption of sintering and to improve the physical and chemical properties of the sinter. In the case of a plant using hematite ores, it seems interesting to produce an hyperbasic sinter and to complete the blast furnace burden with calibrated ore or acid pellets.